Dads' Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO‐D). Issue 4 (17th June 2013) - Anderson, Sheila; Roggman, Lori A.; Innocenti, Mark S.; Cook, Gina A.
ABSTRACT Intervention programs aiming to support fathers' parenting skills with young children need a practical, but psychometrically sound, observational measure of fathers' parenting interactions. The purpose of this study was to test the psychometric properties of the Parenting Interactions with Children—Checklist of Observations Linked to Outcomes (PICCOLO) measure for use with fathers, and to explore whether additional observational father‐behavior items derived from father research and theory would strengthen those psychometric properties. The 29 original PICCOLO items and 44 additional observable behavioral items of early positive father–infant interaction were tested for variability, reliability, and validity, using extant video observations of over 400 ethnically diverse, low‐income fathers. The final measure included 21 items, representing the four domains of positive parenting on the original PICCOLO measure: affection, responsiveness, encouragement, and teaching. Items tested for a playfulness domain did not reach adequate psychometric standards. The final version of the PICCOLO for Dads (PICCOLO‐D) measure demonstrated good reliability and validity, including predictive associations with children's language, cognitive, and socioemotional outcomes into prekindergarten. Findings indicate that the PICCOLO‐D is a psychometricall strong observational measure of early father–child interaction.